History of officials in Tannu-Tuva (in mid 18th – late 19th centuries) - Hovalyg, Salimaa S. (The New Research of Tuva, 2010)
Article deals with the history of formation and evolution of officials in Tuvan society of mid 18th – late 19thcenturies. Author investigates machinery of state, hierarchy of ranks and signs on their distinction.